2014
DOI: 10.1159/000365157
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Antihypertensive Medication Use after Living Kidney Donation through Linked National Registry and Pharmacy Claims Data

Abstract: Background: Use of antihypertensive medications (AHM) after living kidney donation is not well described. Methods: We examined a database wherein national transplant registry data for 4,650 living kidney donors in 1987-2007 were linked to pharmacy claims from a US private health insurer (2000-2007 claims) to identify post-donation AHM fills. Cox regression with left- and right-censoring was used to estimate the frequencies and relative likelihood (adjusted hazards ratios, aHR) of post-donation AHM fills accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…When describing health outcomes to potential living kidney donors, important perspectives include overall event frequencies after donation, within-donor comparisons across donor sub-groups such as race, comparisons of outcomes among donors vs. the general population, and when possible, comparisons of outcomes among donors vs. selected non-donor controls with similar baseline health (Table 3) (20, 38). Due to the rigorous evaluation that donors undergo as part of the selection process, living kidney donors are inherently healthier than the general population, contributing to improved outcomes usually seen in most studies comparing these two populations (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When describing health outcomes to potential living kidney donors, important perspectives include overall event frequencies after donation, within-donor comparisons across donor sub-groups such as race, comparisons of outcomes among donors vs. the general population, and when possible, comparisons of outcomes among donors vs. selected non-donor controls with similar baseline health (Table 3) (20, 38). Due to the rigorous evaluation that donors undergo as part of the selection process, living kidney donors are inherently healthier than the general population, contributing to improved outcomes usually seen in most studies comparing these two populations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[20] b Data from the current study estimating the risk of gout diagnosis based on health care administrative database codes or pharmacy fill for a medication used to treat gout. c Data from Lam et al . estimating the risk of gout diagnosis based on health care administrative database codes.…”
Section: Figurementioning
confidence: 99%
“…Lastly, our non-donor comparisons used general (rather than “healthy”) controls, as we lacked sufficient capture durations to allow for screening and selection of non-donors free of baseline co-morbidity. While general population comparisons do not address risk attributable to donation, as long as the type of comparison is explicit, general population experience can provide one relevant benchmark for framing post-donation outcomes (40,54). …”
Section: Discussionmentioning
confidence: 99%
“…Our study, therefore, provides insight into within-donor comparisons of narcotic use according to factors such as sex, as well as comparisons to the average general population as one commonly used benchmark (14,36,40,55). While we were unable to address the risk of narcotic medication use attributable to donor nephrectomy itself, we examined patterns of primary healthcare diagnoses in the 7 days preceding narcotic prescription fills, and found that the majority of healthcare visits were related to diagnoses such as spinal, joint, and soft tissue complaints.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed research will identify barriers to technological innovations for LKD follow-up and engagement and design the mHealth system thus informing clinical care management and risk mitigation. This is particularly important for AfricanAmerican LKDs who have the highest ESRD risk attributable to donation as well as higher rates of postdonation HTN diagnoses [24].…”
Section: Significance Summarymentioning
confidence: 99%